When the Future Becomes no Longer a Threat but, More, an Opportunity - Terry Trickett (La Tadeo DeArte)
The City of London is entering new and relatively unexplored territory with its intention of making “Culture and Commerce stronger together”. An opportunity to demonstrate this ambition exists at London Wall West, a site in the cultural heart of the Square Mile, but plans drawn up so far have attracted considerable opposition as they involve the demolition of existing buildings. Even though the City stands firm in its conviction that new buildings are required, justifying this approach in a world where construction accounts for 39% of the planet’s global greenhouse emissions is challenging. The proposed answer, “Building Less is More”, will require the City to develop a degree of confidence in the idea that, in part, London Wall West can become virtual. We can anticipate that to design and construct a new virtual world, where people can spend time that is as good as in the outside physical world, London Wall West must become a test bed for experimentation on how to turn “conjecture” into reality. As in the physical world, the creation of a virtual realm depends on defining and understanding the determinants of people’s behavior. Architects are already involved in creating virtual flights of fancy but holding the reins of all those who are unleashing the power of generative artificial intelligence will be the “metaverse curator”–a completely new role to match the task of building “a new and better world”.